Smoking and alcohol use plays a mediating role on the social determinants of high blood pressure: Evidence from nationally representative sample in India - Arivarasan Barathi; Yuvaraj Krishnamoorthy; Rajan Rushender (International Journal of Noncommunicable Diseases)
Background and Aim: A better understanding of the complex interplay between socioeconomic determinants and risk factors of high blood pressure (BP) has critical implications. Behavioral characteristics are strong candidates to act as mediators of the observed effects of socioeconomic determinants on BP; therefore, we aimed to investigate the mediating role of smoking and alcohol on the association between education, wealth index, sex, and hypertension using NFHS-5 data. Materials and Methods: We conducted a secondary analysis of the data collected from a nationally representative survey (NFHS-5 data) in India. We included 1,923,504 people aged 18 years and above who had all the necessary information for the analysis. We performed a mediation analysis using linear and logistic regression models to estimate the natural direct effect, total effects, and natural indirect effect of sex, education, and wealth index, and systolic BP (SBP) and diastolic BP (DBP), while maintaining behavioral habits (smoking and alcohol use) as mediator variables. Results: An equal distribution of males (51.4%) and females (48.6%) was seen, about 13.2% consumed alcohol, and 27.6% had used or smoked tobacco. Females had significantly lower SBP (β = −4.59, −4.67) and DBP (β = −2.07, −2.60) compared to males. Lower educational levels significantly influenced systolic (β = −2.89, −2.89) and diastolic (β = −1.15, −1.14) BP; people in the richer and richest quintile had significantly higher systolic (β = 0.60, 0.59) and diastolic (β = 0.43, 0.43) BP. Mediation analysis showed partial mediation by alcohol and tobacco, which was statistically significant (P < 0.001). Conclusion: These results will help in developing targeted interventions to address the unique risk factors and challenges faced by different population subgroups.